KutaBaca: Developing and Implementation of an Offline Digital Library System to Enhance Literacy in the Low-Connectivity Environment of Wiyata Tech Village Purwakarta - Venica, Liptia; Sodikin, Reisa Aulia; Herlina, Nina; Elviani, Ulva; Zahron, Aulia Aufa; Kurniawan, Muhammad Randy; Nugraha, Ariel Dwika; Putri, Dewi Indriati Hadi (Institut Teknologi Nasional, Bandung, 2026)
Achieving Quality Education (Sustainable Development Goals, or SDGs, Point 4) remains a significant challenge in rural areas characterized by low digital infrastructure. Specifically, Kutamanah Village in Purwakarta faces critical literacy issues, with its primary school's literacy rate tragically categorized as ‘red,’ compounded by a low regional Quality Education Index score of 46.70. This research aims to address this digital and literacy gap through the systematic development and implementation of KutaBaca, an Offline Digital Library system. Utilizing a Research and Development (R&D) methodology based on the Software Development Life Cycle (SDLC) model, the system was designed with a local server and an internal wireless network, allowing students and teachers to access a vast collection of e-books and learning modules without relying on an external internet connection. Evaluation focused on rigorous Functional Testing and a System Usability Scale (SUS) assessment involving 30 students and 7 teachers. The results demonstrate a 100% functional success rate and an overall average SUS score of 83.1 ('Excellent'). This confirms that KutaBaca is a reliable, user-friendly, and replicable technological innovation, effectively increasing access to information and serving as a sustainable solution to boost literacy and support SDGs 4, 10, and 17 in low-connectivity regions.